White Pass & Yukon Railroad at the White Pass summit station, Alaska, April 9, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "White Pass summit. White Pass and Yukon Route. April 9th 99" Original photograph by Eric A. Hegg 700; copied by Webster and Stevens 349.A.